Penyuluhan Strategi Branding Kopi Lokal di Pasar Global bagi Komunitas Teman Kohi - Sophiana Widiastutie; Shanti Darmastuti; Mansur Juned; Anastasya Gabriela Nahampun; Fitri Chaerunisa; Sherina Amellia (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
Marketing strategy is one of the efforts made in expanding product sales both in local and global markets. One strategy that can be done is through branding. Coffee commodities are one of the main commodities of Indonesia's exports. Aside from being the main commodity of exports, business in the field of coffee also increased from time to time. Efforts to expand the local coffee market are one of the focus of business people who come from the community of young people who open a number of coffee businesses. One of them is Komunitas Teman Kohi which is one of the local coffee industry players whose members consist of members of the community of young people and are engaged in coffee entrepreneurs. The problem of branding strategies faced by Komunitas Teman Kohi in expanding market access is an attraction for the devotion team to carry out community service. In this regard, the Community Service Team of Universitas Pembangunan Nasional Veteran Jakarta developed partnership cooperation with Komunitas Teman Kohi in counseling activities on local coffee branding strategies in the global market. In this activity, the community service team distributed pre-test before conducting counseling activities which were then followed by filling in post-test.